Peter Heller papers - Heller, Peter, 1920-; Blos, Peter; Burlingham, Dorothy T.; Erikson, Erik H. (Erik Homburger), 1902-1994.; Freud, Anna, 1895-1982.; Freud, W. Ernest, 1914-; Heller, Peter, 1920-; Rosenfeld, Eva Marie, 1892-1977.; Ross, Victor, 1919-; Schmiderer, Mary Burlingham, 1917-1974.; Valenstein, Katrina Burlingham, 1919-
Correspondence, patient case notes, poetry, and other writings, jottings, drawings and other papers relating chiefly to Anna Freud's psychoanalysis of Heller when he was a child in Vienna, Austria. Includes Heller's first draft of Eine Kinderanalyse bei Anna Freud (A child analysis with Anna Freud; published in 1983). Also includes files concerning the Hietzing School conducted by Dorothy T. Burlingham, Eva Marie Rosenfeld, and Anna Freud in Vienna between 1927 and 1932. The files consist chiefly of correspondence, responses to a questionnaire, and transcripts of interviews of the school's founders, Burlingham and Rosenfeld; its teachers, Peter Blos and Erik H. Erikson; and several of its students including Anna Freud's nephew W. Ernest Freud, Peter Heller, Rosenfeld's son Victor Ross, and Burlingham's daughters Mary (Mabbie Burlingham) Schmiderer and Katrina (Tinky Burlingham) Valenstein.
Author and educator. Born in Vienna; immigrated to the U.S. in 1944. Died 1998.
Collection material in German and English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Sigmund Freud collection.
Keywords: Hietzing School; Child analysis; Education -- Austria -- Vienna; Private schools -- Austria -- Vienna; Psychoanalysis -- Austria -- Vienna; Authors; Educators